2018
DOI: 10.1007/s11695-018-3499-y
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation Adherence and Outcomes Among Pregnant Women After Bariatric Surgery

Abstract: Our data indicate satisfactory adherence to post-op micronutrient supplementation and few gestational complications following BS. Moreover, child's birth weight was not associated with maximum %WL, %WL at conception, or time since BS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…In fact, the increase in PTD is an unexpected consequence considering that obesity is a risk factor for PTD. Macro and micronutrient deficiencies (e.g., vitamins A, B and D, calcium, iron) after BS procedures, especially if not adequately supplemented during pregnancy, probably play a crucial role, as they have been considered risk factors for several fetal complications, such as PTD, LBW, SGA, hypotonia, mental retardation, neural tube defects, microcephaly, IUGR, and intracranial hemorrhages [17]. BS may impact on the pregnancy-related blood metabolites and metabolic pathways, whose concentrations change as pregnancy progresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the increase in PTD is an unexpected consequence considering that obesity is a risk factor for PTD. Macro and micronutrient deficiencies (e.g., vitamins A, B and D, calcium, iron) after BS procedures, especially if not adequately supplemented during pregnancy, probably play a crucial role, as they have been considered risk factors for several fetal complications, such as PTD, LBW, SGA, hypotonia, mental retardation, neural tube defects, microcephaly, IUGR, and intracranial hemorrhages [17]. BS may impact on the pregnancy-related blood metabolites and metabolic pathways, whose concentrations change as pregnancy progresses.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of pregnancies after BS has rapidly increased over the past years and several population-based studies have assessed the impact of BS on perinatal outcomes, the findings of these studies remain controversial [10][11][12][13][14][15]. Recent studies suggested that BS in women with severe obesity may improve both fertility and perinatal outcomes and, specifically, reduce the risks for GDM, preeclampsia, and macrosomia, compared with pregnant obese women who have not undergone BS [16][17][18][19][20][21]. However, dealing with pregnant women who underwent BS poses a crucial clinical challenge and several questions need to be addressed about the impact of BS on other adverse pregnancy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…This will allow associations to be drawn with clinical outcomes in the offspring and provide evidence-based dietary advice. Further investigation of food group intake and analysis of dietary patterns is also warranted, in order to emphasise and optimise nutritional intake from food as much as possible, especially considering that adherence to micronutrient supplementation is poor [59]. The AURORA (bAriatric sURgery in women Of Reproductive Age) study, a prospective cohort study in Belgium, is an example of such a study that can provide data [41,60]; however, other similar studies internationally are also needed.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the prescribed vitamin supplements could either be not fully absorbed or the adherence to these supplements could be lower. Previous research shows that adherence to supplements is only 30% at 6 months after BS and decreases over time, and another study found that only 34.7% of post-bariatric pregnant women adhered to supplementation [28,29]. Hazart et al showed that counseling on vitamin supplementation increased adherence from 23.5% after surgery to 77.8-100% during pregnancy [9].…”
Section: Multivitamin Supplementation Adherencementioning
confidence: 99%